Natural Convection of Temperature-Sensitive Magnetic Fluids in Porous Media (Advances in Applied Mathematics and Mechanics, 2011)
In this article, natural convection of a temperature-sensitive magnetic fluidin a porous media is studied numerically by using lattice Boltzmann method. Resultsshow that the heat transfer decreases when the ball numbers increase. When themagnetic field is increased, the heat transfer is enhanced; however, the averagewall Nusselt number increases at small ball numbers but decreases at large ballnumbers due to the induced flow being more likely confined near the bottom wallswith a high number of obstacles.